Molecular characterization and antimicrobial resistance of Escherichia coli in dairy products of Dhaka, Bangladesh - Hasan, G M M Anwarul; Satter, Mohammed A; Ahmed, Khondoker Shahin (Bangladesh Journal of Scientific and Industrial Research, 2023)
This study aimed to identify and evaluate the occurrence and antibiotic susceptibility of E. coli in various dairy products. Physical, biochemical, and molecular tests were used to identify and characterize the E. coli isolates. The study found that E. coli was present in 16% of raw milk, 8% of cheese, 6% of butter, and 10% of ice cream samples. No E. coli O157:H7 or its toxin stx1 was identified in any samples. The antibiotic susceptibility test revealed that the highest susceptibility was to Azithromycin, Gentamycin, and Ciprofloxacin, while the lowest susceptibility was to Amoxicillin/clavulanic acid, Tetracycline, and Trimethoprim/sulfamethoxazole. Interestingly, 36.84% of E. coli isolates showed multidrug resistance, which is a serious health concern as they may transmit and develop antibiotic resistance in the human body. The study highlights the need for continued surveillance and monitoring of dairy products for food safety and public health purposes. Bangladesh J. Sci. Ind. Res. 58(2), 79-88, 2023